Current Account Imbalances in the Euro Area: Does Catching up Explain the Development?. Issue 1 (23rd January 2013) - Belke, Ansgar; Dreger, Christian
Abstract In the debate on global imbalances, the euro area countries received inreasing attention since the outbreak of the financial crisis. While the current account is on balance for the entire area, divergences between individual member states have increased since the introduction of the common currency and are part of the excessive imbalances procedure. This paper explores the determinants of the imbalances by using paneleconometric techniques. The analysis shows that a lack in competitiveness is the main explanation for the external deficits of the countries that are at the heart of the euro area debt crisis. As a deterioration of competitiveness is not feasible for the surplus countries, an asymmetric response is required to reduce the imbalances.